2021
DOI: 10.1007/s11356-021-16459-w
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of water resistance by Fe2O3/TiO2 photoelectrocatalysts for formaldehyde removal: experimental and theoretical investigation

Abstract: TiO2-based photocatalysts are a potential technology for removing indoor formaldehyde (CHOH) owing to their strong photooxidation ability. However, their photooxidation performance is generally weakened when suffering from the competitive adsorption of H2O. In a method inspired by the oxygen evolution reaction (OER) to generate intermediates with hydroxyl radicals on the anode electrode catalysts, an electric field was employed in this research and applied to the photooxidation of CHOH to prevent the competiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Therefore, the key to addressing this issue is to activate H 2 O molecules and generate hydroxyl radicals, and the OER can produce hydroxyl radicals by extracting hydrogen atoms from H 2 O. 98 Dong 99 enhanced the decomposition of gaseous H 2 O using an extra electric field to generate hydroxyl radicals, thus substantially enhancing the removal of CHOH.…”
Section: The Role Of An Extra Electric Field In the Oxygen Evolution ...mentioning
confidence: 99%
“…Therefore, the key to addressing this issue is to activate H 2 O molecules and generate hydroxyl radicals, and the OER can produce hydroxyl radicals by extracting hydrogen atoms from H 2 O. 98 Dong 99 enhanced the decomposition of gaseous H 2 O using an extra electric field to generate hydroxyl radicals, thus substantially enhancing the removal of CHOH.…”
Section: The Role Of An Extra Electric Field In the Oxygen Evolution ...mentioning
confidence: 99%
“…Although dimer adsorption is more favorable on anatase, monomer adsorption is more stable on Au/TiO 2 . Dong et al 163 demonstrated that a positive electric field with a strength of…”
Section: Water Splittingmentioning
confidence: 99%
“…Although dimer adsorption is more favorable on anatase, monomer adsorption is more stable on Au/TiO 2 . Dong et al 163 demonstrated that a positive electric field with a strength of 0.05 V/Å was preferable to a negative electric field for the production of hydroxyl on Fe 2 O 3 /TiO 2 (010). Fe 2 O 3 decoration can significantly boost hydroxyl formation, resulting from a decrease in the binding energy between the Fe and H 2 O. Non‐metallic materials can also be doped into TiO 2 surfaces and change the adsorption and dissociation characteristics of H 2 O.…”
Section: The Adsorption Activation and Reaction Of Small Inorganic Mo...mentioning
confidence: 99%
“…Compared with conventional catalysts, single-atom catalysts (SACs) exhibit many superior properties, including high catalytic activity, high adsorption selectivity and high metal atom utilization. 24 SACs show excellent performance in fuel cells, 25 electrocatalytic reduction of CO2, 26 and hydrogenolysis. 27 Similarly, SACs exhibit excellent properties in the field of catalytic oxidation: FeSA shows high catalytic activity for the catalysis of benzene, 28 methane, 29 and mercury 30 at room temperature.…”
Section: Introductionmentioning
confidence: 99%